The relationship between knowledge, attitude, and practice toward organic fertilizer adoption among almond smallholder farmers in Uruzgan, Afghanistan - Wasil, Abdul Hadi; Arif Shah, Jasmin; Mohamed Haris, Nur Bahiah (Human Resource Management Academic Research Society, 2022)
Almonds are an important dried fruit and second in the ranking, after raisin and grape, in Afghanistan. The decline in their production is due to low levels of technology adoption, as well as the extreme use and poor timing of inorganic fertilizer application in the Uruzgan Province. Since organic fertilizers are vital to producing quality almonds, this study examined the relationship between the knowledge, attitude, and practice related to the adoption of organic fertilizer. This study applied the technology acceptance model (TAM) and theory of planned behaviour (TPB) to investigate the adoption of organic fertilizer. The Tarin Kowt District was purposively selected, as it represents the top almond-producing district of Uruzgan Province. A multi-stage sampling survey was employed with 116 almond smallholder farmers. The results show a positive and significant effect of practice and knowledge on organic fertilizer adoption. To improve organic fertilizer adoption, knowledge and practice should be advocated among almond smallholder farmers. This research contributes to the demonstration of practical training methods and participation in technology, as training is the most important factor in providing information about organic fertilizer adoption and could have a higher chance of stimulating farmers to adopt organic fertilizers.